NON-LINEAR 3D-FINITE ELEMENT ANALYSIS OF STEEL FIBER REINFORCED CONCRETE MEMEBERS SUBJECTED TO BLAST LOADING - A. Thaker, Tariq; T. Ameen, Abdulla (Iraqi Journal of Civil Engineering, 2005)
Abstract: This research is devoted to investigate the behavior of steel fiber reinforced concrete members subjected to blast loading. Material nonlinearity due to nonlinear response of concrete in compression, tensile cracking, strain softening after cracking, crushing of concrete and the yielding of steel reinforcement are considered. Three-dimensional finite element is used with eight and twenty-node are hexahedral isoparametric brick element for the spatial discretization. In the idealization of the reinforced concrete structures, the steel reinforcement is incorporated in the concrete brick element as a smeared layer assuming perfect bond. Concrete is modeled as an elasto-viscoplastic model in compression and as a linear elastic strain softening in tension. The steel reinforcement is assumed to have uniaxial properties in the direction of the bars. A classical elasto-viscoplastic model is used to model the reinforcement. Some numerical problems are solved and compared with other studies to verify the applicability and accuracy. Parametric study to investigate the effect of some important parameters has been carried out. The results showed that the use of steel fibers in members subjected to dynamic loading lead to better performance.